Patient‐reported dietetic care post hospital for free‐living patients: a Canadian Malnutrition Task Force Study. Issue 1 (19th May 2017) - Keller, H.; Payette, H.; Laporte, M.; Bernier, P.; Allard, J.; Duerksen, D.; Gramlich, L.; Jeejeebhoy, K.
Abstract: Background: Transitions out of hospital can influence recovery. Ideally, malnourished patients should be followed by someone with nutrition expertise, specifically a dietitian, post discharge from hospital. Predictors of dietetic care post discharge are currently unknown. The present study aimed to determine the patient factors independently associated with 30‐days post hospital discharge dietetic care for free‐living patients who transitioned to the community. Methodology: Nine hundred and twenty‐two medical or surgical adult patients were recruited in 16 acute care hospitals in eight Canadian provinces on admission. Eligible patients could speak English or French, provide their written consent, were anticipated to have a hospital stay of ≥2 days and were not considered palliative. Telephone interviews were completed with 747 (81%) participants using a standardised questionnaire to determine whether dietetic care occurred post discharge; 544 patients discharged to the community were included in the multivariate analyses, excluding those who were admitted to nursing homes or rehabilitation facilities. Covariates during and post hospitalisation were collected prospectively and used in logistic regression analyses to determine independent patient‐level predictors. Results: Dietetic care post discharge was reported by 61/544 (11%) of participants and was associated with severe malnutrition [Subjective Global Assessment category C: odd's ratio (OR) 2.43 (1.23–4.83)], weight loss post discharge [(OR 2.86 (1.45–5.62)], comorbidity [(OR 1.09 (1.02–1.17)] and a dietitian consultation on admission [(OR 3.41 (1.95–5.97)]. Conclusions: Dietetic care post discharge occurs in few patients, despite the known high prevalence of malnutrition on admission and discharge. Dietetic care in hospital was the most influential predictor of post‐hospital care.